Vector Surveillance for Lymphatic Filariasis After Mass Drug Administration in an Endemic Area: A Case Study in Bekasi - Endang Puji Astuti; Joni Hendri; Mara Ipa; Andri Ruliansyah; Triwibowo Ambar Garjito (Universitas Airlangga, 2023)
Introduction: Lymphatic Filariasis (LF) re-transmission in endemic areas that have completed mass drug administration (MDA) should be a concern. Entomological data are required to support the elimination of LF. This research aims to present bionomic and evaluative evidence of Wuchereria bancrofti in Culex quinquefasciatus in Bekasi. Methods: Entomological surveys were carried out in Jatimulya Village, Bekasi, from October to November 2019. Female Cx. quinquefasciatus were caught using Human-baited Double Net traps (HDNs) both indoors and outdoors over a 12-hours (from 6 PM to 6 AM). Female mosquitos were subjected to ovary dissection to determine their longevity. In addition, the Man-Hour Density (MHD), Man-Biting Rate (MBR), Daily Survival Rate (DSR), and estimated longevity were calculated. Wuchereria bancrofti was detected using the Polymerase Chain Reaction (PCR) on dissected mosquitos. Results and Discussion: In total 673 female Cx. quinquefasciatus were collected. Culex quinquefasciatus' peak landing time was demonstrated between 12 and 3 AM. The values of Mosquito Parity Rate (MPR) and DSR are 22.88 and 0.692, respectively, implying that the estimated lifespan of dissected mosquitos ranged up to three days. The PCR analysis has revealed that none of the 48 pooled samples of Cx. quinquefasciatus are tested positive for W. bancrofti. Conclusion: Although this survey has found non-existent microfilaria in the LF vector Cx. quinquefasciatus, routine vector monitoring, and surveillance are still required to ensure the long-term viability of the LF elimination program.